Constraining the process of intracontinental subduction in the Austroalpine Nappes: Implications from petrology and Lu‐Hf geochronology of eclogites. (6th October 2021) - Miladinova, Irena; Froitzheim, Nikolaus; Nagel, Thorsten J.; Janák, Marian; Fonseca, Raúl O. C.; Sprung, Peter; Münker, Carsten
Abstract: High‐ and ultrahigh‐pressure rocks occur in the Austroalpine Nappes in a 400 km long belt from the Texel Complex in the west to the Sieggraben Unit in the east. Garnet growth during pressure increase was dated using Lu‐Hf chronometry. The results range between c. 100 and 90 Ma, indicating a short‐lived period of subduction. Combined with already published data, our estimates of metamorphic conditions indicate a field gradient with increasing pressure and temperature from the northwest to the southeast, where the rocks experienced ultrahigh‐pressure metamorphism. The P‐T conditions of the eclogites generally lie on the 'warm' side of the global range of subduction‐zone metamorphic conditions. The oldest Cretaceous eclogites (c. 100 Ma) are found in the Saualpe‐Koralpe area derived from widespread gabbros formed during Permian to Triassic rifting. In the Texel Complex garnets showing two growth phases yielded a Variscan‐Eoalpine mixed age indicating re‐subduction of Variscan eclogite‐bearing continental crust during the Eoalpine orogeny. Jurassic blueschist‐facies metamorphism at Meliata in the Western Carpathians and Cretaceous eclogite‐facies metamorphism in the Austroalpine are separated by a time gap of c. 50 Ma and therefore do not represent a transition from oceanic to continental subduction but rather separate events. Thus, we propose that subduction initiation was intracontinental at the site of a Permian rift.